Silver@graphene oxide nanocomposite-based optical sensor platform for biomolecules - Kamali, Khosro Zangeneh; Pandikumar, Alagarsamy; Sivaraman, Gandhi; Lim, Hong Ngee; Wren, Stephen Paul; Tong, Sund; Huang, Nay Ming (Royal Society of Chemistry, 2015)
In this report, a silver@graphene oxide (Ag@GO) nanocomposite-based optical sensor was developed for the detection of biomolecules such as dopamine (DA), ascorbic acid (AA), and uric acid (UA). An aqueous solution of Ag@GO was prepared using a simple chemical reduction method, and it showed a characteristic surface plasmon resonance (SPR) band at 402 nm. The SPR features of the Ag@GO nanocomposite were used for the detection of DA, AA, and UA. The SPR intensity-based limits of detection (LODs) of DA, AA, and UA were 49 nM, 634 nM, and 927 nM, respectively. The SPR band position-based LODs of DA, AA, and UA were 30 nM, 1.64 μM, and 2.15 μM, respectively. The present optical sensor was more sensitive to DA than to UA and AA. The interactions of the biomolecules with Ag@GO were studied based on density functional theory (DFT), and it was found that DA had more interaction than AA and UA. This novel Ag@GO nanocomposite is simple to prepare and showed excellent stability and sensitivity toward the detection of biomolecules.